A study on consumer behavior in non-face-to-face leisure activities applying the PPM model: Focusing on online music performances - Hyojeong Byun (Global Business & Finance Review (GBFR), 2024)
Purpose: This study applied the PPM model to study consumer behavior in non-face-to-face leisure activities in the era of the coronavirus pandemic. Design/methodology/approach: In order to achieve the purpose of this study, literature research and empirical research were conducted to derive primary measurement items, and an online questionnaire survey was conducted with consumers who had experience in participating in non-face-to-face leisure activities during the coronavirus pandemic using the initially derived PPM model-based factors. Through factor analysis, 5 push factor items, 4 pull factor items, and 3 mooring factor items were derived, and regression analyses were conducted separately for leisure satisfaction and leisure recommendation intention to identify non-face-to-face leisure consumers' behavior intentions. Findings: As a result, it was found that some items of PPM factors had significant influencing relationships with non-face-to-face leisure consumers' leisure satisfaction and recommendation. In addition, satisfaction with non-faceto- face leisure was found to have a positive (+) influencing relationship with recommendation intentions. Research limitations/implications: This study is significant as it is the first to attempt to analyze the leisure behavior of consumers during the COVID-19 pandemic. The study presents motivators and intervening factors that affect leisure behavior from a new perspective based on the changed leisure environment due to the pandemic. However, the study only focused on online music performances when examining non-face-to-face leisure behavior. Therefore, the behavior intentions of other non-face-to-face leisure consumers were not comprehensively understood, and the results of this study cannot be generalized. Originality/value: This study is significant in that it presented non-face-to-face leisure behavior motivation and constraint factors from a new perspective based on the leisure environment changed due to COVID-19, and it is expected that the application of the PPM model and leisure behavior intention can be applied to various tourism and leisure behavior studies hereafter to bring about theoretical expansion.
Keywords: 650; Non-face-to face leisure; Leisure behavior intention; PPM model; COVID-19